2014
DOI: 10.1002/lary.24382
|View full text |Cite
|
Sign up to set email alerts
|

Translational genomics of acquired laryngotracheal stenosis

Abstract: Identification of SNPs associated with development of ALTS will provide new experimental targets to study wound healing in human subjects. The association found in the current study between ALTS and SNP rs1799750 is being validated in a larger population examining an expanded set of relevant SNPs. Identifying patients with genetic susceptibility to ALTS and poor wound healing in the upper airway will be useful for management of patients after upper-airway injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
2
12
1
Order By: Relevance
“…39 Recent discoveries also highlight the potential for a genetic predisposition to laryngotracheal scar formation; one study found an association between a polymorphism in matrix metalloproteinase 1 (MMP1) and the formation of scar after intubation injury. 40 This discovery complements our finding of elevated MMP activity after hypoxic stimulation of normal laryngotracheal fibroblasts, suggesting that genetic predisposition may enhance the effects of hypoxia on the laryngotracheal ECM. Ultimately, we believe that iLTS is multi-factorial disease arising from a combination of genetic predisposition, hypoxic and mechanical tissue injury, and subsequent consequences on local microbiome and inflammation.…”
Section: Discussionsupporting
confidence: 75%
“…39 Recent discoveries also highlight the potential for a genetic predisposition to laryngotracheal scar formation; one study found an association between a polymorphism in matrix metalloproteinase 1 (MMP1) and the formation of scar after intubation injury. 40 This discovery complements our finding of elevated MMP activity after hypoxic stimulation of normal laryngotracheal fibroblasts, suggesting that genetic predisposition may enhance the effects of hypoxia on the laryngotracheal ECM. Ultimately, we believe that iLTS is multi-factorial disease arising from a combination of genetic predisposition, hypoxic and mechanical tissue injury, and subsequent consequences on local microbiome and inflammation.…”
Section: Discussionsupporting
confidence: 75%
“…). Inclusion criteria were 1) a history of endotracheal intubation for at least 3 days, 2) the intubation or tracheotomy had to have occurred at least 30 days before recruitment to ensure adequate time for ALTS to develop in susceptible subjects, and 3) laryngoscopy, bronchoscopy, or radiologic studies must have documented the presence or absence of ALTS in the medical record …”
Section: Methodsmentioning
confidence: 99%
“…This study excluded patients with congenital subglottic stenosis, idiopathic subglottic stenosis, chronic inflammatory and autoimmune diseases such as Wegener's granulomatosis, idiopathic pulmonary fibrosis, sarcoidosis, cicatricial pemphigoid, relapsing polychondritis, and patients who have received radiation therapy to the head or neck …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations